80.3k views
0 votes
Does anyone know how to solve this ?

Does anyone know how to solve this ?-example-1

1 Answer

4 votes

9514 1404 393

Answer:

see below

Explanation:

Make use of the quadratic formula.

For equation ax² +bx +c = 0, the solutions are ...


x=(-b\pm√(b^2-4ac))/(2a)

Here, you have a=1, b=-1, c=1, so the solutions are ...


x=(-(-1)\pm√((-1)^2-4(1)(1)))/(2(1))=(1\pm√(1-4))/(2)=(1\pm i√(3))/(2)\\\\\boxed{x=(1+i√(3))/(2)\text{ and }x=(1-i√(3))/(2)}

Does anyone know how to solve this ?-example-1
User Jassi Oberoi
by
6.3k points